A Biphasic Mercury‐Ion Sensor: Exploiting Microfluidics to Make Simple Anilines Competitive Ligands. Issue 41 (21st August 2015) - Petzoldt, Martin; Eschenbaum, Carsten; Schwaebel, S. Thimon; Broedner, Kerstin; Lemmer, Uli; Hamburger, Manuel; Bunz, Uwe H. F.
Abstract Combining the molecular wire effect with a biphasic sensing approach (analyte in water, sensor‐dye in 2‐methyltetrahydrofuran) and a microfluidic flow setup leads to the construction of a mercury‐sensitive module. We so instantaneously detect Hg2+ ions in water at a 500 μM concentration. The sensor, conjugated non‐water soluble polymer 1 (XFPF), merely supports dibutylaniline substituents as binding units. Yet, selective and sensitive detection of Hg2+‐ions is achieved in water. The enhancement in sensory response, when comparing the reference compound 2 to that of 1 in a biphasic system in a microfluidic chip is >103. By manipulation of the structure of 1, further powerful sensor systems should be easily achieved.